Differences of the EU-Georgia and the EU-Armenia Relations - Khasiyeva, Günel (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
The cooperation between the European Union and Georgia and Armenia began with the collapse of the Soviet Union and communism. The first steps in cooperation were a Partnership and Cooperation Agreement signed in 1999 and the Technical Assistance to the Commonwealth of Independent States program, the technical and financial assistance for implementation of economic reforms and democratization. Later, the countries were included in the European Neighborhood Policy, the Eastern Partnership, Association Agreements and Deep and Comprehensive Free Trade Agreement. However, Armenia refused to sign Association Agreement in 2013 and joined Eurasian Customs Union (EACU) Russian led. On the other side, Georgia gained allowance for visa-free travel within the Schengen zone in March 2017. The thesis focuses on answering the research question “What explains the varying level of progress in the relations between the EU and Georgia and the EU and Armenia?” It researched all factors affected the process of Europeanization in Armenia and Georgia and analyzed their political background, achievements and obstacles during the cooperation with the EU. The thesis applies qualitative method of research with the use of content analysis of primary sources. Europeanization and EU external governance provide the theoretical tools necessary for analyzing the different levels of progress made in the relationship between the countries and the EU.

ÖZ: Avrupa Birliği, Gürcistan ve Ermenistan arasındaki işbirliği Sovyetler Birliği ve komünizmin çöküşüyle başlamıştı. İşbirliğindeki ilk adımlar, 1999'da imzalanan Ortaklık ve İşbirliği Anlaşması ve uygulamaya konulan ekonomik reformlar ve demokratikleşme için teknik ve mali yardım olan TACIS programıdır. Daha sonra ülkeler, Doğu Komşuluk Politikası, Doğu Ortaklığı, Ortaklık Anlaşması ve Derin ve Kapsamlı Serbest Ticaret Alanında yer almıştır. Buna rağmen, Ermenistan 2013'te Ortaklık Anlaşması imzalamayı reddetmiştir ve Avrasya Gümrük Birliği'ne (EACU) liderlik eden Rusya'ya katılmıştır. Öte yandan Gürcistan, Aralık 2017'de Schengen bölgesinde vizesiz seyahat için izin almıştır. Tez, AB ile Gürcistan ve AB ile Ermenistan arasındaki ilişkilerde değişen ilerleme seviyesini anlatmaktadır ve araştırma sorusuna cevap vermeye odaklanmaktadır. Ermenistan ve Gürcistan'da Avrupalılaşma sürecini etkileyen tüm faktörleri araştırmış ve siyasi geçmişlerinde, başarılar ve engellerle karşılaşılmıştır. Tez, nitel araştırma yöntemini, antlaşmalar, anlaşmalar, raporlar gibi birincil kaynakların içerik analizi kullanarak uygulamaktadır. Avrupalılaşma ve AB dış yönetimi, ülkeler ve AB arasındaki ilişkide kaydedilen farklı ilerlemeleri analiz etmek için gerekli teorik araçları sağlamaktadır.
Master of Arts in International Relations. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of International Relations, 2017. Supervisor: Assist. Prof. Dr. Nuray Ibryamova.
Keywords: Political Science and International Relations; European Union--Political Relations--Armenia--Georgia; European Union countries--Foreign relations; Europeanization; Armenia; Georgia; the European Union; the European Neighborhood Policy; the Eastern Partnership; Association Agreements and DCFTA